Both an N-terminal 65-kDa domain and a C-terminal 30-kDa domain of SecA cycle into the membrane at SecYEG during translocation - Eichler, Jerry (The National Academy of Sciences of the USA, 1997)
SecA, a 102-kDa hydrophilic protein, couples the energy of ATP binding to the translocation of preprotein across the bacterial inner membrane. SecA function and topology were studied with metabolically labeled [(35)S]SecA and with inner membrane vesicles from cells that overexpressed SecYEGDFyajC, the integral domain of preprotein translocase. During translocation in the presence of ATP and preprotein, a 65-kDa N-terminal domain of SecA is protected from proteolytic digestion through insertion into the membrane, as previously reported for a 30-kDa C-terminal domain [Economou, A. & Wickner, W. (1994) Cell 78, 835–843]. Insertion of both domains occurs at saturable SecYEGDFyajC sites and is rapidly followed by deinsertion. SecA also associates nonsaturably and unproductively with lipid. In the presence of ATP, yet without involvement of preprotein or SecYEG, lipid-bound SecA forms domains that are protease-resistant and that remain so even upon subsequent membrane disruption. Unlike the [(35)S]SecA that inserts into the membrane at SecYEGDFyajC as it promotes preprotein translocation, lipid-associated [(35)S]SecA does not chase from its protease-resistant state upon the addition of excess SecA. The finding that two domains of SecA (which together represent most regions of the polypeptide chain) cycle into the membrane during preprotein translocation, as well as the distinction between the membrane association of SecA at translocation sites of SecYEGDFyajC and at nonproductive lipid sites, are fundamental to the study of the role of SecA in preprotein movement.